Factors that Contribute to Spontaneous Platelet Aggregation and Streptokinase-Induced Aggregation in Whole Blood - Armstrong, Ruth; May, Jane A; Lösche, Wolfgang; Heptinstall, Stan (Thrombosis and Haemostasis, 1995)
When whole blood is stirred there is a “spontaneous” platelet aggregation (SPA) which is presumed to be caused by proaggregatory factors released from platelets and other blood cells. Adding streptokinase (SK) to stirred whole blood frequently increases the rate and extent of the platelet aggregation that occurs; this is likely to be via immune complex formation between SK and natural anti-SK antibodies leading to increased release of pro-aggregatory factors.In this investigation we have examined the effects of several inhibitors and antagonists in an attempt to identify the proaggregatory factors that contribute to both SPA and SK-induced aggregation (SKA) and to evaluate different means of inhibiting both processes. The effects of the inhibitors/antagonists were determined in vitro after adding them to citrated whole blood obtained from healthy volunteers. Platelet aggregation was measured using a platelet counting technique.Inhibition of both SPA and SKA by apyrase and by FPL 66096 (a P2T receptor antagonist) demonstrated the involvement of ADP in both processes. Inhibition by chlorpromazine indicated that the most likely source of the ADP is red cells. The effects of sulotroban (a TXA2 antagonist) indicated involvement of TXA2 in SKA but not in SPA. The lack of effect of specific antagonists at S2, α2 and PAF receptors suggested lack of involvement of serotonin, catecholamines and plateletactivating factor in either SPA or SKA. Both SPA and SKA were potently inhibited by low concentrations of iloprost (a PGI2 analogue), but a high concentration of SIN-1 (a NO donor) was much less effective. SPA and SKA were prevented by EDTA and by RGDS indicating the importance of divalent cations and of the RGD sequence in adhesive proteins in mediating the platelet aggregation that occurred.We also determined the effects on SPA and SKA of adding MgCl2 to whole blood. In this case we used blood containing hirudin as anticoagulant. MgCl2 (1 mM) appeared to delay the onset of SPA and markedly inhibited SKA.